Peran Politik terhadap Pengembangan dan Implementasi Kurikulum - Septriyan Anugrah; Nizwardi Jalinus; Rijal Abdullah; Mudjiran Mudjiran; Diah Anggraini Austin; Rayendra Rayendra (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
Efforts to improve the quality of education continue to be carried out by the government, one form of this effort is the development and review of the curriculum so that it is under the times. Several factors underlie curriculum development, including philosophical, psychological, socio-cultural, political, state development and world development, and science and technology (IPTEK) foundations. The process of changing the curriculum in various countries cannot be adapted to the political conditions in that country, therefore the educational curriculum may change at any time according to the political conditions that affect the country concerned. This study aims to analyze and describe the influence of politics on curriculum development in the National Education System. This research is qualitative research using a literature study approach. Furthermore, data were collected through document study.